Phụ phẩm từ sắn là nguồn thức ăn tiềm năng trong chăn nuôi bò ở Cộng hoà dân chủ nhân dân Lào - Phanthavong Vongsamphanh (2019)
The research study was aim to improve utilisation of cassava byproducts in development of sustainable cattle feeding regimes in Lao PDR and other countries with similar conditions. There were four experiments presented on the dissertation. Experiments I, was evaluatr by test for finding the potential of feeding value of the storage cassava pulp in an open pit. Experiment II was study of intake, growrate in local yellow cattle by measure the response of cattle performance on bitter cassava foliage or/and brewers’ grains as a source of bypass protein and fiber supplements to cassava pulp-urea basal diet